Using the abstraction hierarchy to identify how the purpose and structure of road transport systems contributes to road trauma. (December 2019) - Salmon, Paul M.; Read, Gemma J.M.; Stevens, Nicholas; Walker, Guy H.; Beanland, Vanessa; McClure, Rod; Hughes, Brett; Johnston, Ian R.; Stanton, Neville A.
Abstract: Research is beginning to demonstrate the merits of considering the broader road transport system when attempting to understand and prevent road trauma. This study involved the use of Work Domain Analysis, a systems analysis method, to develop a model of a road transport system based on Queensland, Australia. The model was subsequently used to identify the system wide contributory factors that play a role in road crashes, and to identify aspects of road transport systems that could be exploited when developing road safety interventions. The findings show that there are a set of crash contributory factors relating to the raison d'etre, values, and functions of road transport systems. This suggests that further significant reductions in road trauma will only be achieved through fundamental changes to the road transport system itself. Examples discussed include reducing the emphasis on the use of road transport for economic growth, reducing motor vehicle use and increasing active transport modes, and overhauling road safety strategies. Highlights: An abstraction hierarchy model of road transport systems was developed. We used the model to identify crash contributory factors and interventions. Factors relating to the purpose and values of road transport were found. The model suggests fundamental change is required to reduce road trauma. Examples include reducing the emphasis on economic growth and motor vehicle use.